Rationale for Prolonged Glucocorticoid Use in Pediatric ARDS: What the Adults Can Teach Us - Schwingshackl, Andreas; Meduri, Gianfranco Umberto (Frontiers in Pediatrics, 2016)
Based on molecular mechanisms and physiologic data, a strong association has been established between dysregulated systemic inflammation and progression of acute respiratory distress syndrome (ARDS). In ARDS patients, glucocorticoid receptor-mediated downregulation of systemic inflammation is essential to restore homeostasis, decrease morbidity and improve survival and can be significantly enhanced with prolonged low-to-moderate dose glucocorticoid treatment. A large body of evidence supports a strong association between prolonged glucocorticoid treatment-induced downregulation of the inflammatory response and improvement in pulmonary and extrapulmonary physiology. The balance of the available data from eight controlled trials (n = 622) provides consistent strong level of evidence for improving patient-centered outcomes and hospital survival. The sizable increase in mechanical ventilation-free days (weighted mean difference, 6.48 days; CI 95% 2.57–10.38, p < 0.0001) and intensive care unit-free days (weighted mean difference, 7.7 days; 95% CI, 3.13–12.20, p < 0.0001) by day 28 is superior to any investigated intervention in ARDS. For treatment initiated before day 14 of ARDS, the increased in hospital survival (70 vs. 52%, OR 2.41, CI 95% 1.50–3.87, p = 0.0003) translates into a number needed to treat to save one life of 5.5. Importantly, prolonged glucocorticoid treatment is not associated with increased risk for nosocomial infections (22 vs. 27%, OR 0.61, CI 95% 0.35–1.04, p = 0.07). Treatment decisions involve a tradeoff between benefits and risks, as well as costs. This low-cost, highly effective therapy is familiar to every physician and has a low risk profile when secondary prevention measures are implemented.